Unsupportive parenting and internalising behaviour problems in children with or without intellectual disability. Issue 12 (13th September 2016) - Rodas, N. V.; Zeedyk, S. M.; Baker, B. L.
Abstract: Background: Children with intellectual disability (ID) are at heightened risk for developing other psychological disorders, including internalising disorders. Anxiety and depression have been shown to be familial, and parenting is a contributing factor to the development of these disorders. To extend this research, we examined the extent to which mother and father depression and negative, unsupportive parenting related to child internalising behaviour problems, in children with ID or with typical development (TD). Method: Participants were 156 mother and father dyads and their children, assessed at ages 4 and 5 years. We examined parent (mother and father) and child delay status (ID and TD) in relation to measures of both observed and self‐reported unsupportive, negative parenting. Utilising moderation models, we examined the relationship between parental depression, unsupportive/negative parenting and child internalising behaviour problems. Results: Unsupportive, negative parenting differed based on parent gender and child delay status. In addition, father depression was a significant moderator of the relationship between unsupportive parenting and child internalising behaviour problems. Conclusions: Children with ID were found to be at higher risk of experiencing unsupportive, negative parenting than children with TD. Children of depressed fathers were especially vulnerable to developing internalising behaviour problems in an unsupportive parenting context.